If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2v + 2u + 5u = 0 Reorder the terms: 2u + 5u + 2v = 0 Combine like terms: 2u + 5u = 7u 7u + 2v = 0 Solving 7u + 2v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2v' to each side of the equation. 7u + 2v + -2v = 0 + -2v Combine like terms: 2v + -2v = 0 7u + 0 = 0 + -2v 7u = 0 + -2v Remove the zero: 7u = -2v Divide each side by '7'. u = -0.2857142857v Simplifying u = -0.2857142857v
| 79x-76=90 | | x^2+20x+4800=0 | | 78x+76=89 | | x+84=-82 | | x-3=2(x-4) | | 34x-68=79 | | -18=3(3x-3) | | 5(5x+1)=-20 | | P^4-14p^2+40=0 | | -4x+28=-x+7 | | 57x-98=978 | | 45x+78=980 | | 45x+78=98 | | 2c^4-6c^3-12c^2+36c=0 | | 67x+34=173 | | 67x+34=67 | | 6x+43=55 | | 6x+43=45 | | 6x+43=345 | | 6x+43=34 | | 5x+8y=3965 | | 23x-5=34 | | 3x-y=10x+6 | | 5x-41=8x | | 75-30=45 | | (7x+4)(4x-7)= | | 25+75+-90=35 | | x^7+8=-64 | | (3x+5)(x-9)= | | 11x-8=24 | | -16=7b+12 | | 8x+6=0.75 |